Determinants of environmental psychology on green consumer behavior: the moderating role of generation cohort among generation X, Y, and Z - Daniar, Katherin; Triwidyati, Endang (Manajemen dan Bisnis, 2026)
This study aims to explore the Green Consumer Behavior (green purchase intention) of Generation X, Y, Z on three sectors business restaurant, fashion, and hotels in Indonesia. The conceptual model is developed to examine the relationship of green consumer behavior on purchase intention, using generation cohort as moderating variable. The study analyzed 300 samples, determined by quota sampling, using PLS-SEM modeling. The result show that Self Identity, Knowledge, and Environmental Concern have a significant impact on green purchase intention. However, the study found no significant effect from peer influence on green purchase intention. The study reveals that Knowledge has significant in 3 Generations, self identity and environtmental concern have impact in Gen X and Z. Peer influence has no significant in 3 generations. This study emphasizes the critical role of generational cohort on green purchase intention. This paper presents an analysis of Green Consumer Behavior of Generation X, Y and Z in Indonesia. These findings are expected to contribute to the formulation of effective and efficient marketing strategies to increase sales and create a competitive advantage